Interferon gamma upregulates frataxin and corrects the functional deficits in a Friedreich ataxia model - Tomassini, Barbara (Oxford University Press, 2012)
Friedreich's ataxia (FRDA) is the most common hereditary ataxia, affecting ∼3 in 100 000 individuals in Caucasian populations. It is caused by intronic GAA repeat expansions that hinder the expression of the FXN gene, resulting in defective levels of the mitochondrial protein frataxin. Sensory neurons in dorsal root ganglia (DRG) are particularly damaged by frataxin deficiency. There is no specific therapy for FRDA. Here, we show that frataxin levels can be upregulated by interferon gamma (IFNγ) in a variety of cell types, including primary cells derived from FRDA patients. IFNγ appears to act largely through a transcriptional mechanism on the FXN gene. Importantly, in vivo treatment with IFNγ increases frataxin expression in DRG neurons, prevents their pathological changes and ameliorates the sensorimotor performance in FRDA mice. These results disclose new roles for IFNγ in cellular metabolism and have direct implications for the treatment of FRDA.